The Involvement of Xanthone and (E)-Cinnamoyl Chromophores for the Design and Synthesis of Novel Sunscreening Agents - Popiół, Justyna (Int J Mol Sci, 2020)
Excessive UV exposure contributes to several pathological conditions like skin burns, erythema, premature skin aging, photodermatoses, immunosuppression, and skin carcinogenesis. Effective protection from UV radiation may be achieved with the use of sunscreens containing UV filters. Currently used UV filters are characterized by some limitations including systemic absorption, endocrine disruption, skin allergy induction, and cytotoxicity. In the research centers all over the world new molecules are developed to improve the safety, photostability, solubility, and absorption profile of new derivatives. In our study, we designed and synthesized seventeen novel molecules by combining in the structures two chromophores: xanthone and (E)-cinnamoyl moiety. The ultraviolet spectroscopic properties of the tested compounds were confirmed in chloroform solutions. They acted as UVB or UVA/UVB absorbers. The most promising compound 9 (6-methoxy-9-oxo-9H-xanthen-2-yl)methyl (E)-3-(2,4-dimethoxyphenyl)acrylate) absorbed UV radiation in the range 290–369 nm. Its photoprotective activity and functional photostability were further evaluated after wet milling and incorporation in the cream base. This tested formulation with compound 9 possessed very beneficial UV protection parameters (SPF(in vitro) of 19.69 ± 0.46 and UVA PF of 12.64 ± 0.32) which were similar as broad-spectrum UV filter tris-biphenyl triazine. Additionally, compound 9 was characterized by high values of critical wavelength (381 nm) and UVA/UVB ratio (0.830) thus it was a good candidate for broad-spectrum UV filter and it might protect skin against UVA-induced photoaging. Compound 9 were also shown to be photostable, non-cytotoxic at concentrations up to 50 µM when tested on five cell lines, and non-mutagenic in Ames test. It also possessed no estrogenic activity, according to the results of MCF-7 breast cancer model. Additionally, its favorable lipophilicity (miLogP = 5.62) does not predispose it to penetrate across the skin after topical application.